Evaluation and implementation of a membrane filter method for Cronobacter detection in drinking water. Issue 1 (22nd April 2013) - Liu, Hui; Yang, Yuelian; Cui, Jinghua; Liu, Lanzheng; Liu, Huiyuan; Hu, Guangchun; Shi, Yuwen; Li, Jian
Abstract A membrane filter (MF) method was evaluated for its suitability for qualitative and quantitative analyses of Cronobacter spp. in drinking water by pure strains of Cronobacter and non‐Cronobacter, and samples spiked with chlorinated Cronobacter sakazakii ATCC 29544. The applicability was verified by the tests: for pure strains, the sensitivity and the specificity were both 100%; for spiked samples, the MF method recovered 82.8 ± 10.4% chlorinated ATCC 29544 cells. The MF method was also applied to screen Cronobacter spp. in drinking water samples from municipal water supplies on premises (MWSP) and small community water supplies on premises (SCWSP). The isolation rate of Cronobacter spp. from SCWSP samples was 31/114, which was significantly higher than that from MWSP samples which was 1/131. Besides, the study confirmed the possibility of using total coliform as an indicator of contamination level of Cronobacter spp. in drinking water, and the acquired correct positive rate was 96%.